Fosinopril reduces left ventricular mass in untreated hypertensive patients: a controlled trial - Cheung, Bernard M Y (Blackwell Science Inc, 1999)
AIMS: Left ventricular hypertrophy is a powerful predictor of cardiovascular morbidity and mortality. We tested the hypothesis that fosinopril, an angiotensin-converting enzyme inhibitor, reduces left ventricular mass in hypertensive patients. METHODS: Thirty-three patients with untreated mild essential hypertension were randomised to treatment with oral fosinopril (10 mg–20 mg daily) or placebo for 12 weeks. The primary outcome measure was the change in left ventricular mass index determined by echocardiography. RESULTS: Diastolic blood pressure changed from 95.5±2.1 mmHg at baseline to 96.6±2.8 mmHg at the final visit in control patients and changed from 96.6±2.3 mmHg to 91.5±3.0 mmHg in patients treated with fosinopril (P= 0.04). Systolic blood pressure changed from 147.4±3.2 mmHg at baseline to 152.7±4.4 mmHg at the final visit in control patients and changed from 157.6±5.1 mmHg to 149.1±6.1 mmHg in patients treated with fosinopril (P=0.02). Fosinopril reduced diastolic pressure by 6.3 (95%CI 0.3–12.4) mmHg and systolic pressure by 13.3 (95%CI 2.7–23.8) mmHg compared with placebo. The left ventricular mass index changed from 110.0±8.3 g m(−2) to 113.1±8.7 g m(−2) in the control patients and changed from 120.8±5.8 g m(−2) to 109.0±7.5 g m(−2) in patients treated with fosinopril (P=0.02). Fosinopril reduced left ventricular mass index by 14.9 (95%CI 2.2–27.6) g m(−2) compared with placebo. There was no significant change in the left ventricular systolic or diastolic function, nor were there any significant changes in plasma electrolytes and renal function. CONCLUSIONS: Treatment with fosinopril for 12 weeks reduced left ventricular mass significantly in hypertensive patients.